The Look After Yourself (LAY) intervention to improve self-management in stroke survivors: Results from a quasi-experimental study. Issue 6 (June 2020) - Messina, Rossella; Dallolio, Laura; Fugazzaro, Stefania; Rucci, Paola; Iommi, Marica; Bardelli, Roberta; Costi, Stefania; Denti, Monica; Accogli, Monia Allisen; Cavalli, Enrica; Pagliacci, Donatella; Fantini, Maria Pia; et al.
Highlights: International clinical guidelines recommend to offer training to improve self-management skills in stroke survivors. Self-management interventions for stroke survivors vary in timing, duration and setting according to the literature. "LAY intervention" improved self-efficacy, mental health and daily life activities in stroke survivors in hospitalization. Patients with higher education benefited more from "LAY intervention" than from usual care. Abstract: Objective: To test the efficacy of a self-management intervention for stroke survivors vs. usual care. Methods: Using a quasi-experimental study, participants were recruited from three public Italian hospitals. Questionnaires assessing self-efficacy (SSEQ), quality of life (SF-12), physical performance (SPPB), depression (GDS) and activities of daily living (MBI) were administered at baseline, discharge and two months after discharge. Mixed models with a propensity score were used between experimental group (EG) and control group (CG). Logistic models were used to compare the use of health services. Results: Eighty-two stroke survivors were enrolled in the EG and 103 in the CG. Self-efficacy in self-management improved in the EG compared to the CG during hospitalization. Improvements from baseline to discharge were found in the EG in the mental component of SF-12 and in MBI. The EG were 8.9 times more likely to contact general practitioners after discharge and 2.9 times to do regular exercise than CG. Notably, EG with higher education benefitted more from the intervention. Conclusion: The intervention was efficacious in improving self-efficacy, mental health and activities of daily living. Practice implications: Structured educational interventions based on problem-solving and individual goal setting may improve self-management skills in stroke survivors.